Investigating the origin of breakage of panes subjected to blast loading by acoustic emission testing - Jan Dirk van der Woerd (Challenging Glass Conference, 2020)
The Fraunhofer EMI shock-tube facility “Blast-STAR” is used to simulate blast loadings from high explosive detonations similar to realistic conditions. Mainly tests on explosion-resistant safety glazing and façades are carried out. Due to the extreme conditions during the test, it is not trivial to accurately analyze the specimen reaction and in particular to determine the start of breakage of the glass pane. Usually high-speed footage is used for this purpose. Since the size of tested elements is increasing, the determination of place and time of breakage becomes more challenging. Monk and Clubley successfully used piezo transducers in an alternative approach to measure the shock wave originating from glass breakage for detecting the point of initial cracking. They used long-duration blasts, characterized by small peak pressures and a long positive phase duration. In contrast, the blast waves generated with the “Blast-STAR” are characterized by higher peak pressures and a considerable shorter positive phase. The presented work examines the applicability of the approach for the “Blast-STAR” experiments and the accuracy compared to video recordings. Within the paper five shock tube tests are described and evaluated. The results and the experimental set-up are discussed and an outlook for further research is given.